The Types of Nonverbal Communication Cues with Reference to Refugeeism (Raparin Journal of Humanities (RJH), 2020)
This paper tackles nonverbal communication cues among refugees. It is widely believed that nonverbal communication is one of the most effective types of communication to enhance better human understanding and cooperation. Besides, interpretation and comprehension of this type of communication are crucial among diverse nations, cultures, and ethnic groups. On the other hand, the number of refugees has increased because of several factors, mainly including armed political conflicts in Middle-Eastern countries. Thus, they face political, economic, social, and/or psychological threats. Besides, they encounter other challenging difficulties in verbal and nonverbal communication. Therefore, communication enhancement has become essential and crucial to treat refugees through more proactive nonverbal communication strategies. The study targets real people in Sulaimani Governorate refugee camps, Kurdistan Region of Iraq. It investigates the types of nonverbal cues in the sociopragmatic refugeeism context. It initiates by some definitions of sociopragmatics and nonverbal communication and its cues categorization. In addition, it extends to explain the impact of sociopragmatic variables on the communicative types of nonverbal cues.